MEANS AND METHODS OF FORMATION OF MORAL AND LEGAL KNOWLEDGE IN THE CONTINUOUS EDUCATION SYSTEM (International conference on multidisciplinary science, 2023)
In the socio-philosophical literature, the concept of "innovative thinking" is widely used as a new category representing the intellectual abilities of a person at the current stage of society's development. Innovative thinking is a creative activity of society members aimed at creating material and spiritual wealth based on a new way of thinking, as a result of which the effectiveness of introducing innovations into the working process of existing systems becomes a priority.